Optimizing Gingival Biotype Using Subepithelial Connective Tissue Graft: A Case Report and One-Year Followup - Harpreet Singh Grover; Anil Yadav; Priya Yadav; Prashant Nanda (Case Reports in Dentistry)
Gingival recession is the exposure of root surfaces due to apical migration of the gingival tissue margins. The principal objectives of treating a gingival recession are to achieve better esthetics and reduce hypersensitivity. The gingival biotype is an important modifying factor in the treatment of gingival recession. The purpose of this paper is to highlight the significance of changing the soft tissue biotype to a more favorable one while attempting root coverage, to achieve more stable and long-lasting results using subepithelial connective tissue graft.